Patterning of Paternal Investment in Response to Socioecological Change - Schacht, Ryan; Davis, Helen E.; Kramer, Karen L. (Frontiers in Ecology and Evolution, 2018)
Human paternal investment, and that of many other species, is facultatively expressed and dependent on a diverse array of individual, social, and ecological conditions. Well-documented are the various ways in which men invest in offspring and the household. Specifically, local ecology structures pay-offs to male investment and has been shown to be an important predictor of the sexual division of labor. However, while variability in paternal investment has been well-characterized cross-culturally, plasticity within a group in response to changing socioecological conditions remains largely unstudied. To address this, we use recent economic development and market access to explore how changes in socioecology alter behavioral options for men and their resultant investment decisions. Among the monogamous Maya, we find that, associated with the introduction of novel subsistence opportunities and incentives for intensified paternal investment, fathers spend more time in the household, more time in domestic activities and more time interacting with their children. The changes in paternal investment documented here are largely contingent on four conditions: increased efficiency in subsistence brought about by mechanized farming, limited opportunities to engage in wage labor, increased opportunities to invest in offspring quality, and a monogamous mating system. Thus, Maya fathers appear to repurpose found time by furthering investment in their families.